Misonidazole and MTDQ in combination: cytotoxic and radiosensitizing properties in hypoxic mammalian cells. - Astor, M. (Nature Publishing Group, 1979)
A combination of misonidazole and MTDQ (6,6'-methylene-bis-2,2,4 trimethyl-1,2-dihydroquinoline) has been tested for its radiation-sensitizing properties and cytotoxicity, using Chinese hamster V79 cells cultured in vitro. Both compounds sensitize hypoxic cells to the effects of X-rays, and when used in combination their sensitizing properties are additive. By contrast, the presence of MTDQ completely inhibits the cytotoxicity that misonidazole exhibits towards hypoxic cells. These experiments shed some light on the mechanism of action of electron-affinic hypoxic cell sensitizers, and the combination of radiosensitizers suggested may have an application in human cancer radiotherapy by eliminating the neurotoxicity experienced by patients receiving misonidazole during radiotherapy.